ANALISIS IMPLEMENTASI PROGRAM KAMPUNG IKLIM UNTUK MENINGKATKAN DERAJAT KESEHATAN MASYARAKAT DI KORONG PASA - Ismike Suci (Jurnal Kependudukan dan Pembangunan Lingkungan, 2020)
The health sector is vulnerable to the impacts of climate change, 17 % of cases of high diarrhea are a result of climate change, so that climate change adaptation and mitigation to the health and environmental is very important. This study aims to explore implement the of “climate village” program to improve the health status of community in Pasa Surau village, Padang Pariaman regency in the year 2018.This research used mixed method, approach used concurrent triangulation strategy design. The population in this study were all family heads in Pasa Surau village. The sample in this study was 80 family heads. Sampling was done by simple random sampling technique. Quantitative data was processed by univariate analysis, and qualitative data used content analysis.The results showed that community implementation of climate change adaptation of the community is good, with total score is 76.9%. Whereas climate change mitigation is categorized as not good with score is 50%. Management of “climate village” program did not well, because of the lack of human resources and finance issues. By implement “climate village” program, it is hoped to the community to improve adaptation and mitigation behavior to the impact of climate change. Therefore, community participation can be improved by provide knowledge sharing about adaptation and mitigation. Suggestion for the management of “climate village” program to add cadres to the succesfull of this program.